Responding to Quiet Students: Implications for Educators and Advisors - Lisa A. Ruth-Sahd (Adult Education Research Conference, 2014)
Quiet students seldom speak in class and rarely approach the instructor. Educators may find such students perplexing because it is difficult to discern if they are fostering such students’ learning. This paper compares and contrasts introversion and shyness, explores ways in which quiet tendencies influence students’ learning, and lastly, presents implications for teachers and advisors.